2020
DOI: 10.3390/rs12244154
|View full text |Cite
|
Sign up to set email alerts
|

Ground Validation and Error Sources Identification for GPM IMERG Product over the Southeast Coastal Regions of China

Abstract: The Integrated Multi-satellitE Retrievals for the Global Precipitation Measurement mission (IMERG) has been widely evaluated. However, most of these studies focus on the ultimate merged satellite-gauge precipitation estimate and neglect the valuable intermediate estimates which directly guide the improvement of the IMERG product. This research aims to identify the error sources of the latest IMERG version 6 by evaluating the intermediate and ultimate precipitation estimates, and further examine the influences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 24 publications
(39 reference statements)
4
8
0
Order By: Relevance
“…Sui et al. (2020) demonstrated the systematic errors brought by the passive microwave sources of IMERG precipitation data from different sensors, and examined the influences of topography and surface type on these errors. Lu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Sui et al. (2020) demonstrated the systematic errors brought by the passive microwave sources of IMERG precipitation data from different sensors, and examined the influences of topography and surface type on these errors. Lu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the IMERG performance in representing precipitation over ZJP was affected by the orographic conditions, which was consistent with the earlier studies over other regions (e.g., Milewski et al ., 2015; Navarro et al ., 2020; Sui et al ., 2020; Zhou et al ., 2020; Derin et al ., 2021; 2022; Ma et al ., 2021; Li et al ., 2022). For example, both IMERG‐L and IMERG‐F had larger underestimations over the mountainous areas of ZJP (Figure S1), accompanied by relatively poor categorical metrics‐based performance (i.e., lower POD and larger FAR).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ERA5 precipitation data show highest performance over subregions of temperate monsoon climate and temperate continental climate over China mainland (Xu et al, 2022). Moreover, the performance of model‐based precipitation products significantly outperform satellite‐based products over high‐latitude regions in cold seasons (Gao et al, 2020; Ma et al, 2022; Sui et al, 2020; Zhu et al, 2021). Therefore, ERA5 could convincingly stand out among many state‐of‐the‐art global and regional precipitation products obtained through gauge‐based, satellite‐based, and atmospheric retrospective‐analysis models, as well as through the merging of their products (Hersbach et al, 2020; Chen et al, 2008; Harris et al, 2020; Huffman et al, 2007; Huffman et al, 2019; Kobayashi et al, 2015; Ma et al, 2020; Ma et al, 2022, shown in Table 1) in terms of long time series with high quality.…”
Section: Methodsmentioning
confidence: 99%